Anti-inflammatory effects of newly synthesized α-galacto-oligosaccharides on dextran sulfate sodium-induced colitis in C57BL/6J mice. (July 2018) - Dai, Zhuqing; Feng, Simin; Liu, Anna; Wang, Hong; Zeng, Xiaoxiong; Yang, Chung S.
Abstract: α-Galacto-oligosaccharides have been reported to have beneficial health effects. The purpose of this study was to investigate the preventive effects of a newly synthesized α-galacto-oligosaccharide mixture (α-GOSg), as well as raffinose family oligosaccharides (RFOs), on dextran sulfate sodium (DSS)-induced colitis in mice. When administered in drinking water at 0.5% for 15 days, both α-GOSg and RFOs significantly decreased fecal hemoglobin content, partially prevented colon length shortening, reduced the severity of colon inflammation, and attenuated DSS-induced upregulation of cyclooxygenase-2. In addition, the activation of the inflammatory regulator nuclear factor-kappa B was slightly inhibited by α-GOSg. The results showed that the newly synthesized α-GOSg preparation has similar anti-inflammatory activities as RFOs in this colitis model. The anti-inflammatory activity of α-GOSg in humans remains to be investigated. Graphical abstract: Highlights: Newly synthesized α-galacto-oligosaccharides (α-GOSg) alleviates colitis in mice. α-GOSg has comparable activities than raffinose family oligosaccharides. Anti-inflammatory effects of α-GOSg are associated with suppression of COX-2.